An Assessment of Clinical Research Self-Efficacy among Researchers at the Largest Healthcare Institute in Qatar: Recommendations and Future Actions - Seba Qussini (16727773) (2024)
Objectives Clinical research professionals must be equipped with adequate training in sound scientific methods and appropriate ethics. In this study, we aimed to assess the current clinical research self-efficacy of researchers at Hamad Medical Corporation (HMC). We also evaluated the effects of training courses on researchers’ self-efficacy. Methods Utilizing a cross-sectional design, we used the shortened Clinical Research Appraisal Inventory (CRAI-12) through an online survey to assess the current clinical research self-efficacy of 600 researchers at HMC, Doha, Qatar. After conducting descriptive analyses, unpaired t test and ANOVA were used to determine significant mean percentages between variables. Pearson correlation coefficients were also calculated to measure the association among the interval variables. All tests were 2-sided, and significance was defined as P < .05. Results For all questions, except those related to “funding,” most participants scored on the upper half of the scale (>5), reflecting higher self-efficacy for the topics covered in CRAI. Gender differences were significant across all factors, with males reporting higher levels of self-assessed efficacy and in clinical research. Other factors such as higher education degrees and previous (external) clinical research training were also associated with higher self-reported clinical research efficacy. Conclusions The findings of this study indicate that researchers at HMC possess high clinical research self-efficacy overall, but lower self-efficacy in securing funding. Gender and education level positively influence self-efficacy across CRAI factors. Notably, clinical research training boosts self-efficacy, especially when obtained outside HMC. In conclusion, healthcare providers are strongly encouraged to engage in effective clinical research training courses, both within and outside of their healthcare institutions, to improve their clinical research efficacy and enhance clinical practice. Other Information Published in: Journal of Medical Education and Curricular Development License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/23821205241233425